Heteronymous h temporal reflex as sign of hyperexcitability in ALS. Issue 1 (January 2019) - Barone, T.; Libonati, L.; Fanella, G.; Pozzilli, V.; Fiorini, I.; Di Bari, S.; Goglia, M.; Romano, M.; Masini, E.; Tartaglia, G.; Cambieri, C.; Ceccanti, M.; et al.
Abstract : The stimulation of masseteric nerve elicits an H reflex (Hr) both in the masseter muscle and in the temporalis muscle. The heteronymous Hr can be used to assess the excitability of α -MN and it can be considered a sign of upper motor neuron involvement in ALS patients. The aim of this study is to analyze the presence of this reflex in ALS patients and in normal subjects. We enrolled 29 ALS patients and 38 normal subjects. We recorded the Hr and M-wave from masseter and temporalis muscle response, by the stimulation of the masseteric nerve. We found a statistically significant difference in the excitability of heteronymous H reflex which was more elicitable in ALS patients than in healthy people of the same age. Brisk jerk is considered a sign of α -MN hyperexcitability in corticospinal tract damage. In ALS patients, damage of the corticospinal tract produces an enhanced Hr that it is more easily recorded than in normal subjects.